Distinguishing histopathologic features of acantholytic dermatoses and the pattern of acantholytic hypergranulosis. (5th November 2018) - See, Sharlene Helene C.; Peternel, Sandra; Adams, Derrick; North, Jeffrey P.
Abstract : Background: Acantholysis can be seen in multiple skin diseases. Adnexal acantholysis has been regarded as a feature distinguishing pemphigus vulgaris (PV) from acantholytic conditions. Methods: A retrospective review of the histopathologic features of diseases with acantholysis including PV, pemphigus foliaceus (PF), Hailey‐Hailey disease (HHD), Darier disease (DD), Grover disease, and pityriasis rubra pilaris (PRP) was performed. Results: Biopsies of PV (n = 49), HHD (n = 27), DD (n = 25), Grover disease (n = 65), and PRP (n = 33) showed suprabasilar acantholysis. Acantholysis was limited to the lower epidermis in PV and PRP, and involved all epidermal layers in HHD, DD, and Grover disease. Acantholysis in PF (n = 38) mainly involved the upper epidermis. Follicular acantholysis occurred more frequently in PV and PF ( P < 0.0001). Eccrine acantholysis was found in PV (42%), HHD (18%), PF (13%), and DD (4%). Grover disease, DD, and HHD had greater dyskeratosis ( P < 0.0001). Neutrophils were more common in PV, PF, and HHD, while eosinophils were more common in Grover disease and DD. A pattern termed acantholytic hypergranulosis occurred predominantly in PF. Conclusion: Adnexal acantholysis does not reliably distinguish PV from PF. The level of acantholysis, degree of dyskeratosis, and acantholytic hypergranulosis are distinguishing features between the two types of pemphigus and other acantholytic disorders.